Kajian Literatur tentang Penerapan Media Pembelajaran Matematika untuk Meningkatkan Hasil Belajar Penjumlahan pada Siswa Sekolah Dasar - Diyana Putri Santoko; Selfilia Ramadhani; Nurul Aisyiyah; Nandinia Nurul Aisyah; Anida Nur’aina; Eyria Dwi R (Universitas PGRI Madiun, 2026)
Low achievement in addition among elementary school students is one of the issues that requires the use of effective instructional media to help students understand mathematical concepts in a concrete way. This study aims to analyze the application of various mathematics instructional media, identify the most commonly used types of media, and examine their impact on elementary school students’ achievement in addition. This study employed a Systematic Literature Review (SLR) method by analyzing 15 scientific articles obtained through Google Scholar using the Publish or Perish application, covering the publication period from 2020 to 2026. The research stages included article identification, screening based on inclusion and exclusion criteria, quality assessment, data extraction, and qualitative descriptive analysis. The results of the study indicate that learning media such as number cards, Tangga Pintar, Pos Jumlah, congklak, Domjum Cards, instructional videos, Pohon Pintar, real-world objects, the PAPINJUR Game, SPINKOJA, flashcards, flannel boards, Mobil Hitung, and PAPINKA are effective in improving students’ learning outcomes in addition. In addition, the use of instructional media also contributes to increasing students’ motivation, active participation, engagement, and understanding of mathematical concepts. Concrete materials combined with educational games are the most widely used type of instructional media and have proven highly effective in teaching addition in elementary school. Thus, the use of instructional media tailored to students’ characteristics can support more effective, engaging, and meaningful mathematics learning.